1994
DOI: 10.1017/s0143385700007719
|View full text |Cite
|
Sign up to set email alerts
|

Positivity conditions for polynomials

Abstract: We study several notions of positivity for a class of real-valued functions of several variables that includes the Laurent polynomials. We show that Handelman's positivity condition is characterized by boundedness of the associated Legendre transformation, or boundedness of the entropy function, while another notion of positivity here introduced characterizes the mapping property of the Legendre transformation derived by Marcus and Tuncel for beta functions. Several examples are given to distinguish the variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…In fact, it is shown in [3,Theorem 6.4] that if f is strongly positive on a neighborhood of r , then σ > 0 (that theorem was stated and proved for polynomials, but the same proof can be used verbatim for power series).…”
Section: Asymptotic Expansions For Certain Integralsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it is shown in [3,Theorem 6.4] that if f is strongly positive on a neighborhood of r , then σ > 0 (that theorem was stated and proved for polynomials, but the same proof can be used verbatim for power series).…”
Section: Asymptotic Expansions For Certain Integralsmentioning
confidence: 99%
“…It can be shown that if f is the pointwise spectral radius of an irreducible matrix whose entries are polynomials with positive integral coefficients (the beta function of Tuncel, see [10]), then µ f and σ f are closely related to the entropy and information variance of the associated Markov chain. The function µ f is the Legendre transformation of f (see, e.g., [3]). …”
Section: Asymptotic Expansions For Certain Integralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positivity conditions for polynomials with real coefficients play a key role in several branches of mathematics, such as real algebraic geometry, convex geometry, probability theory and optimization, and have been widely studied (see e.g. [3,9,11,15,16,17,18,19,20,23,24] and the references therein). An interesting and important class of polynomials are those whose coefficients are positive.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…It is proved in [1,Theorem 6.4] that strong positivity on an open interval containing r is enough to ensure that σ f (r) > 0. Hence for strongly positive polynomials, μ f provides a bijection from (0, ∞) to (0, deg f ).…”
Section: Introductionmentioning
confidence: 99%